Illicit Trade in Wartime: Ukraine’s Trends and Challenges for Counteraction - Шостко, Олена Юріївна; Шостко, О. Ю.; Shostko, Olena Yu.; Дрьомін, Віктор Миколайович; Дрьомін, В. М.; Dryomin, Viktor M.; Мельничук, Тетяна Володимирівна; Мельничук, Т. В.; Melnychuk, Tetiana V.; Дунаєва, Тетяна Євгенівна; Дунаєва, Т. Є.; Dunaieva, Tetiana Ye. (Cambridge University Press, 2025)
This theoretical and empirical study describes and explains the patterns of changes in domestic illicit trade and related transnational illicit flows of goods, services and money during the extreme social crises based on the case of the war in Ukraine. Depending on the legal status of the civil circulation of items, illicit trade is categorized into two groups: illicit (criminal) trade outside the economic sphere; and illicit (illegal) trade within the economic sphere. Typical destructive practices and their peculiarities during the war are considered in each group of illicit trade with the use of quantitative and qualitative methods. In terms of the dichotomy “war as a cause and consequence of crime”, this article addresses significant transformations in established criminal activities outside the official economy, such as drug trafficking and human trafficking, while also highlighting newly emerging crimes, specifically the illegal movement of conscripts across national borders. Furthermore, the article explores illegal trade within the economy, focusing on the trade in excisable goods and the new growing issue of abuse of humanitarian aid. The authors discuss the main deficiencies in adequate counteraction related to both war circumstances and systematic problems of state institutions, in particular, the criminal justice system.
Shostko O. Yu. Illicit Trade in Wartime: Ukraine’s Trends and Challenges for Counteraction / O. Yu. Shostko, V. M. Dryomin, T. V. Melnychuk et al. // International Annals of Criminology. – Published online by Cambridge University Press, 2025. – 63(1). - P. 75-106. URL: https://doi.org/10.1017/cri.2025.7
Keywords: illicit trade; illegal trade; Ukraine; crime; war